PERILAKU SIMBOLIK KOMUNITAS KREATIF TELEMATIKA (Studi Fenomenologi Relasi Antarpelaku Di Kota Malang) - Dodot Sapto Adi; Budi Siswanto (Universitas Merdeka Malang, 2018)
Abstract The phenomenon of the creative community of telematics in the city of Malang is more interesting because it is in the process of social-cultural shift to metropolitan. This initiates the renewal of community positions and life as research urgency, focusing on constructing symbolic behaviors expressed as social and cultural products. The research process begins by conducting a scientific study in synthetic literacy, which collects information on several research reports and published scientific papers, and then conducts research using phenomenology method to formulate verification of the results with 12 informants considering the level of activity of informants pursue the field of activities, especially creative photography and videography. The research results of the creative community of telematics still need an effort to give space openly for its members for participation, with high awareness for its social role. It has strengthened the relational principle that gave birth to a growing community tradition in an alliances to grow in community empowerment, demonstrating efforts: (1) expanding member opportunities in intercommunity relationships through individual and group levels; (2) enhancing community image through facilitation forums that have a positive impact on the growth of inter-community integration; and (3) to maintain values based on mutual commitment and develop them into the identity of reformers. Keywords: creative community of telematicsDOI : https://doi.org/10.26905/nomosleca.v4i1.2072